Urokinase-type plasminogen activator contributes to heterogeneity of macrophages at the border of damaged site during liver repair in mice - Kawao, Naoyuki; Nagai, Nobuo; Tamura, Yukinori; Okada, Kiyotaka; Yano, Masato; Suzuki, Yasuhiro; Umemura, Kazuo; Ueshima, Shigeru; Matsuo, Osamu (Thrombosis and Haemostasis, 2011)
Urokinase-type plasminogen activator (u-PA) plays an important role in tissue remodelling through the activation of plasminogen in the liver, but its mechanisms are less well known. Here, we investigated the involvement of u-PA in the accumulation and phenotypic heterogeneity of macrophages at the damaged site during liver repair. After induction of liver injury by photochemical reaction in mice, the subsequent pathological responses and expression of phenotypic markers in activated macrophages were analysed histologically. Fibrinolytic activity at the damaged site was also examined by fibrin zymography. In wild-type mice, the extent of damage decreased gradually until day 14 and was associated with an accumulation of macrophages at the border of the damaged site. In addition, the macrophages that accumulated near the damaged tissue expressed CD206, a marker of highly phagocytic macrophages, on day 7. Further, macrophages that were adjacent to CD206-positive cells expressed inducible nitric oxide synthase (iNOS), a pro-inflammatory marker. u-PA activity increased at the damaged site on days 4 and 7, which distributed primarily at the border region. In contrast, in u-PA-deficient mice, the decrease in damage size and the accumulation of macrophages were impaired. Further, neither CD206 nor iNOS was expressed in the macrophages that accumulated at the border region in u-PA-deficient mice. Mice deficient for the gene encoding either u-PA receptor (u-PAR) or tissue-type plasminogen activator experienced normal recovery during liver repair. These data indicate that u-PA mediates the accumulation of macrophages and their phenotypic heterogeneity at the border of damaged sites through u-PAR-independent mechanisms.
Keywords: u-PA; macrophage accumulation; macrophage activation; macrophage heterogeneity; liver repair